Tumor microenvironment promotes lymphatic metastasis of cervical cancer: its mechanisms and clinical implications - Li, Yuting; Gao, Xiaofan; Huang, Yibao; Zhu, Xiaoran; Chen, Yingying; Xue, Liru; Zhu, Qingqing; Wang, Bo; Wu, Mingfu (Frontiers in Oncology, 2023)
Although previous studies have shed light on the etiology of cervical cancer, metastasis of advanced cervical cancer remains the main reason for the poor outcome and high cancer-related mortality rate. Cervical cancer cells closely communicate with immune cells recruited to the tumor microenvironment (TME), such as lymphocytes, tumor-associated macrophages, and myeloid-derived suppressor cells. The crosstalk between tumors and immune cells has been clearly shown to foster metastatic dissemination. Therefore, unraveling the mechanisms of tumor metastasis is crucial to develop more effective therapies. In this review, we interpret several characteristics of the TME that promote the lymphatic metastasis of cervical cancer, such as immune suppression and premetastatic niche formation. Furthermore, we summarize the complex interactions between tumor cells and immune cells within the TME, as well as potential therapeutic strategies to target the TME.